2006
DOI: 10.1016/j.jsat.2006.05.018
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year evaluation of a methadone medical maintenance program

Abstract: Methadone medical maintenance (MMM) is a model for the treatment of opioid dependence in which a monthly supply of methadone is distributed in an office setting, in contrast to more highly regulated settings where daily observed dosing is the norm. We assessed patient characteristics and treatment outcomes of an MMM program initiated in the Bronx, New York, in 1999 by conducting a retrospective chart review. Participant characteristics were compared with those of patients enrolled in affiliated conventional me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
0
20
0
4
Order By: Relevance
“…In BC, carries are more often prescribed in rural areas and may be a necessary component in the reintegration of clients into society, as copayments are required once an individual gains employment. Several studies conducted in the United States have demonstrated success with "methadone medical maintenance" prescribing long carries (up to 1 month) in stabilized, responsive patients (Harris et al, 2006). Evidence on the public safety issues regarding carry prescriptions should be balanced against evidence that supports their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In BC, carries are more often prescribed in rural areas and may be a necessary component in the reintegration of clients into society, as copayments are required once an individual gains employment. Several studies conducted in the United States have demonstrated success with "methadone medical maintenance" prescribing long carries (up to 1 month) in stabilized, responsive patients (Harris et al, 2006). Evidence on the public safety issues regarding carry prescriptions should be balanced against evidence that supports their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Le traitement de substitution aux opioïdes a fait l'objet de très nombreuses évaluations et son efficacité a pu être démon-trée dans plusieurs contextes culturels différents (Fiellin & al., 2001 ;Gruer & al., 1997 ;Harris & al., 2006 ;Langendam & al., 1998 ;McMurphy, Shea, Switzer, & Turner, 2006 ;Merrill & al., 2004 ;Plomp, Van Der Hek, & Herman, 1996 ;Sheridan, Goodyear-Smith, Butler, Wheeler, & Gohns, 2008 ;Wittchen & al., 2008). Ce traitement consiste à proposer un produit de remplacement qui pénètre progressivement dans l'organisme, qui ne produit pas de sensation euphorisante et qui maintient le consommateur dans un état fonctionnel (Paquin, 2003).…”
Section: Le Traitement De Substitutionunclassified
“…La situation rapportée semble correspondre en plusieurs points à celle observée aux États-Unis en rapport avec la légis-lation fédérale qui encadre le traitement de substitution (Fiellin & al., 2001 ;Fiellin, O'Connor, Chawarski, & Schottenfeld, 2004 ;Harris & al., 2006 ;King & al., 2006 ;McMurphy, Shea, Switzer, & Turner, 2006 ;Merril & al., 2004). Ces politiques visent à prévenir la vente illégale des médications de substitution et à assurer la présence d'un accompagnement psychosocial à la pharmacothérapie (Harris & al., 2006).…”
Section: Forces Et Limitesunclassified
See 1 more Smart Citation
“…The mechanism of action by which MET can alleviate opioid dependence and diminishing symptoms in affected individuals, have been discussed thoroughly [4][5][6][7][8]. MET has also been used for the relief of moderate-to-severe pain [9][10][11][12][13][14]. Thus, the increased use and availability of the drug might explain the more frequent MET overdose cases in children and adults [15][16][17].…”
Section: Introductionmentioning
confidence: 99%